PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING ( GUIDED DISCOVERY ) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 2 KAMPAR - Sari, Titin Maida; ', Erviyenni; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to know the improvement of students learning achievement in Hydrocarbon subject at class X of SMAN 2 Kampar by applying guided discovery learning model. This research used Randomized Control Group Pretest-Posttest design. This research was conducted in SMAN 2 Kampar. The samples of the research were the students of class X2 as experimental class and the students of class X5 as control class. Experimental class is a class which was applied the guided discovery learning model while control class was not given the treatment. Data analysis technique that is used in this research is t-test. Based on the result of the data analysis, it found out that tcount > ttable which is 5.54 > 1.68. It means that the application of guided discovery learning model can improve students’ learning achievement in Hydrocarbon subject at class X of SMAN 2 Kampar with high category of the improvement of learning achievement (N-Gain) which is 0.74.Key Words: Guided Discovery, Learning Achievement, Hydrocarbons.